2017
DOI: 10.1155/2017/7968450
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Verification of CAPN1 and CAST Gene Polymorphisms in Different Generations of Da-Heng Broilers

Abstract: The micromolar calcium activated neutral protease (CAPN1) and calpastatin (CAST) have been widely regarded as genes related to muscle growth and meat tenderness. The objective of this study was to verify the association of SNPs of CAPN1 and CAST genes with carcass and tenderness traits and search the possible change patterns of SNPs in CAPN1 and CAST genes in six generations of broiler breeding process for growth rate, efficiency, and reproduction, during the third generation and the ninth generation, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 34 publications
0
6
0
2
Order By: Relevance
“…Observing this result, we think that long-term artificial selection may lead to reduced nucleotide diversity in these commercial chicken breeds. Although the DH is a commercial chicken breed, it was bred by Sichuan Dahen Poultry Breeding Co., Ltd, located at Hanchang Town, Chengdu City of Sichuan Province, using Chinese indigenous breeds, and only had a short-term artificial selection (Zhou et al, 2017). The PXY maybe suffered a longterm or high-strength artificial selection in the genetic resources conservation procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Observing this result, we think that long-term artificial selection may lead to reduced nucleotide diversity in these commercial chicken breeds. Although the DH is a commercial chicken breed, it was bred by Sichuan Dahen Poultry Breeding Co., Ltd, located at Hanchang Town, Chengdu City of Sichuan Province, using Chinese indigenous breeds, and only had a short-term artificial selection (Zhou et al, 2017). The PXY maybe suffered a longterm or high-strength artificial selection in the genetic resources conservation procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Teknik PCR yang dilakukan mengacu pada Zhou et al (2017) dengan menggunakan primer CAST forward 5'-CCAAAAGTAGATGAACATTCT-3' dan reverse 5'-GCTTCTATTAATTCCTACT-3'. Sampel DNA sebanyak 45 yang didapat dari tiga jenis ayam kampung disequencing dengan menggunakan mesin sekuenser (ABI Prims 3100-Avant Genetic Analyzer) pada fragmen primer forward dan reverse.…”
Section: Metodeunclassified
“…Some studies have been revealed the associations of the CAST polymorphism with carcass traits and meat quality in many livestock [15]; [16]; [17]; [18]; [19] and [19]. Recently, some of the SNPs in the CAST gene have been included as commercial genetic markers by some livestock industries [20]. It should be noted, that the existence of a similar association in sheep has been reported in only a few research papers to date [21]; [13]; [14].…”
Section: Introductionmentioning
confidence: 99%